Analysis of Delayed Bleeding after Endoscopic Submucosal Dissection for Gastric Epithelial Neoplasms. (8th February 2012) - Mukai, Shinichi; Cho, Songde; Kotachi, Takahiro; Shimizu, Akinori; Matuura, Genta; Nonaka, Michihiro; Hamada, Toshihide; Hirata, Ken; Nakanishi, Toshio
Abstract : Aim . Delayed bleeding after endoscopic submucosal dissection (ESD) for gastric epithelial neoplasms is a major complication. We investigated factors related to post-ESD bleeding to identify preventive measures. Methods . The study included 161 gastric epithelial neoplasms in 142 patients from June 2007 to September 2010. Post-ESD bleeding was defined as an ulcer with active bleeding or apparent exposed vessels diagnosed by an emergency endoscopy or a planned follow-up endoscopy. We analyzed associations between bleeding and the following factors: age, sex, morphology, pathology, tumor depth, ulcer presence/absence, location, size of the resected lesion, duration of the procedure, the number of times bleeding occurred during ESD, and the use of anticoagulants and/or antiplatelet drugs. Subsequently, we examined characteristics of bleeding cases. Results . Post-ESD bleeding occurred in 21 lesions. Univariate analysis of these cases showed that ulcer presence/absence (P < 0.001 ), middle or lower third lesions (P = 0.036 ), circumference (P = 0.014 ), and a post-ESD ulcer with an extended lesser curve (P = 0.009 ) were significant predictors of bleeding. Multivariate analysis showed that ulcer presence/absence (OR 9.73, 95% CI 2.28–41.53) was the only significant predictor. Conclusion . Ulcer presence/absence was considered the most significant predictor of post-ESD bleeding.